Nesting biology of the Hooded Crow Corvus corone cornix in a mixed residential–agricultural area in southern Sweden - Hessel, Rebecca; Elmberg, Johan (Ornis Svecica, 2010)
We studied 11 active and 29 old nests of Hooded Crows Corvus corone cornix in a mixed residential-farmland landscape (3.6 km2) in southern Sweden in 2009. The density of active nests was 3.06/km2 land area and 7.33/km2 forest area. Thirty-eight nests were in pine-dominated forest and two in private gardens. All nests (active and old) were in pine trees Pinus sylvestris, and sample plots around nest trees had the following characteristics (means): 350 tree stems/hectare, 1,487 bushes/ hectare, and canopy cover 8%. Distance to the nearest active Crow nest averaged 234 m, but variation was large. Mean distance from nests to nearest forest edge was 19 m and to the nearest inhabited building 68 m. Nests were placed near the tree top (mean height 11 m) in all cardinal directions but with a significant bias towards the south. Seven out of 11 (64%) active nests produced fledglings (mean 1.2 nestling/successful nest). Breeding success was higher in nests that were close to another crow nest. Compared with previous studies, hatching success was high but final fledgling production was low.